Effect of surface treatment with boiling alkaline solution on electrochemical properties of the ZrNi alloy electrode. (22nd June 2016) - Matsuyama, Akihiro; Mizutani, Hironori; Kozuka, Takumi; Inoue, Hiroshi
Abstract: Electrochemical properties of the ZrNi alloy electrode with the boiling alkaline treatment were investigated. The boiling alkaline treatment was performed by immersing ZrNi powder or electrode in a boiling 6 M KOH aqueous solution for 4 h. During the boiling alkaline treatment, the bulk structure of the ZrNi powder, the B33 -type (CrB) structure, remained, whereas the outer ZrO2 native surface was replaced by Ni(OH)2 . The initial discharge capacity at 10 mA g −1 and 333 K for the ZrNi alloy electrode was increased from 18 to 320 mAh g −1 by the boiling alkaline treatment. However, cycle performance got worse, because the ZrNi alloy particles were pulverized for the charge–discharge cycles. Highlights: The ZrNi powder or electrode was immersed in a boiling 6 M KOH aqueous solution. The outer ZrO2 native surface was replaced Ni(OH)2 by the boiling alkaline treatment. The initial discharge capacity at 333 K for the surface treated ZrNi electrode was 320 mAh g −1 . The ZrNi alloy particles were pulverized for the charge–discharge cycles.